A Note on Emerging Hydrographic Technology and Applications - Casey, Michael J. (The International Hydrographic Review, 2001)
The Objective of the IHO ’s Committee on Hydrographic Research in Information Systems (CHRIS) Technology Assessment Working Group (TAWG) is to assess the potential of present and developing information technology and applications. TAWG makes technology assessment reports to CHRIS every two years. This note summarizes the November, 2000 report.